BERRYA ROXB. and CARPODIPTERA GRIS. - a. j. g. h. kostermans (Research Center for Biology, 1969)
In his monographic treatment of Tiliaceae, Burret in Notizbl. bot.Gart. Berlin 9: 607. 1926) pointed out the close affinity of Berrya andCarpodiptera, the former represented in Asia and the Pacific area, thelatter from Africa and America.",